Sudden cardiac death and late arrhythmias after the Fontan operation. (22nd August 2016) - Pundi, Kavitha N.; Pundi, Krishna N.; Johnson, Jonathan N.; Dearani, Joseph A.; Li, Zhuo; Driscoll, David J.; Wackel, Philip L.; McLeod, Christopher J.; Cetta, Frank; Cannon, Bryan C.
Abstract: Objectives: We sought to examine the incidence and predictors of arrhythmias and sudden cardiac death (SCD) after Fontan operation. Background: Arrhythmias and SCD have been reported following operations for congenital heart disease, but the incidence and risk factors have not been well defined in patients after a Fontan operation. Methods: We reviewed records of all patients who had a Fontan operation from 1973 to 2012 ( n  = 1052) at our institution. A questionnaire was mailed to patients who were not known to be deceased at the initiation of the study. Late arrhythmias were classified as bradyarrhythmias or tachyarrhythmias requiring treatment >30 days after operation. Results: We included 996/1052 (95%) patients with no arrhythmia diagnosis prior to Fontan. Overall 10‐, 20‐, and 30‐year freedom from arrhythmias was 71%, 42%, and 24%, respectively. Of 864 patients who survived >30 days after Fontan, 304 (35%) had atrial flutter, 161 (19%) had atrial fibrillation, 108 (13%) had atrial tachycardia, 37 (4%) had reentrant supraventricular tachycardia, 40 (5%) had ventricular tachycardia, and 113 (13%) had sinus node dysfunction. Predictors of late arrhythmias included an atriopulmonary Fontan, age at operation (>16 years) or atrial arrhythmias postoperatively. During follow‐up, 52/1052 (5%) patients had SCD, with 51 having documentation available; 8 patients died suddenly within 30 days and the remaining 43 had an average time to SCD of 6.9 ± 6.7 years (median was 3.8 years). Arrhythmias were documented in 28/43 (65%) patients prior to SCD. Predictors of SCD included atrioventricular valve replacement and post‐bypass Fontan pressures >20 mm Hg; preoperative sinus rhythm was protective. Conclusions: Arrhythmias and SCD are significant concerns among Fontan patients and specific risk factors may warrant closer follow‐up and earlier consideration for therapy.